Gestational Age Variation in Human Placental Drug Transporters - Laura Goetzl; Nune Darbinian; Nana Merabova; Lindsay C. Devane; Sammanda Ramamoorthy (Frontiers Media S.A., 2022)
Patient and providers' fear of fetal exposure to medications may lead to discontinuation of treatment, disease relapse, and maternal morbidity. Placental drug transporters play a critical role in fetal exposure through active transport but the majority of data are limited to the 3rd trimester, when the majority of organogenesis has already occurred. Our objective was to define gestational age (GA) dependent changes in protein activity, expression and modifications of five major placental drug transporters: SERT, P-gp, NET, BCRP and MRP3. Apical brush border membrane fractions were prepared from fresh 1st, 2nd and 3rd trimester human placentas collected following elective pregnancy termination or planned cesarean delivery. A structured maternal questionnaire was used to identify maternal drug use and exclude exposed subjects. Changes in placental transporter activity and expression relative to housekeeping proteins were quantified. There was evidence for strong developmental regulation of SERT, NET, P-gp, BCRP and MRP3. P-gp and BCRP decreased with gestation (r = −0.72, p < 0.001 and r = −0.77, p < 0.001, respectively). Total SERT increased with gestation but this increase was due to a decrease in SERT cleavage products across trimesters. Uncleaved SERT increased with GA (r = 0.89, p < 0.001) while cleaved SERT decreased with GA (r = −0.94, p < 0.001). Apical membrane NET overall did not appear to be developmentally regulated (r = −0.08, p = 0.53). Two forms of MRP3 were identified; the 50 kD form did not change across GA; the 160 kD form was steady in the 1st and 2nd trimester and increased in the 3rd trimester (r = 0.24, p = 0.02). The 50 kD form was expressed at higher levels. The observed patterns of SERT, NET P-gp, BCRP and MRP3 expression and activity may be associated with transporter activity or decreased placental permeability in the 1st trimester to transporter specific substrates including commonly used psychoactive medications such as anti-depressants, anti-psychotics, and amphetamines, while transport of nutrients and serotonin is important in the 1st trimester. Overall these observations are consistent with a strong protective effect during organogenesis. 3rd trimester estimates of fetal exposure obtained from cord blood likely significantly overestimate early fetal exposure to these medications at any fixed maternal dose.